RELATIONSHIP BETWEEN PHYSICAL ACTIVITY AND BODY VITALS AMONG UNDERGRADUATE STUDENTS AT RIVERS STATE UNIVERSITY (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
This study explores the correlation between physical activity levels and key body vitals among undergraduate students at Rivers State University. Utilizing a cross-sectional design, data were collected from 300 students through self-reported physical activity questionnaires and direct measurements of body vitals, including heart rate, blood pressure, and body mass index (BMI). The analysis revealed a significant positive relationship between regular physical activity and improved body vitals. Students who engaged in moderate to vigorous physical activity exhibited lower resting heart rates, optimal blood pressure levels, and healthier BMI ranges compared to their less active peers. These findings underscore the importance of physical activity in maintaining and enhancing physiological health among university students. The study highlights the need for targeted interventions and policies to promote physical activity within the university setting to foster better health outcomes. Future research should investigate the long-term effects of sustained physical activity on body vitals and academic performance.